Communal Favourite Things: Food Gifts and Consumption History in Seventeenth Century Northwest Bohemia - Maegraith , Janine (Dějiny – teorie – kritika, 2017)
The potential of food gifts in shedding light on food history has been emphasised by Natalie Zemon Davis and Felicity Heal, amongst others. Food constituted one of the main expenses of a household in early modern Central Europe; researching daily decisions and food provisions is therefore important to understand early modern living conditions. While inventory studies allow insight into people’s everyday life and well-being, the everyday practices of food consumption remain obscure and the historiography leaves some questions unanswered. Looking at food gifts could provide new perspectives and complement the existing historiography. The analysis of food gifts could also show what meaning the material goods given as gifts had in people’s lives and how this fit into the local economy. Ego-documents seem a convenient source since they indicate what was important to the author at the time. An analysis of the memoir of Michael Stüeler (1629–1649), which contains numerous references to food gifts, serves as an experiment to explore everyday practices in food exchange and consumption in Central Europe. By looking at the possibility of a “marketplace of gift giving”, it can also serve to understand the complexity of the early modern economy.